PENDIDIKAN PENGASUH PADA PANTI SOSIAL ASUHAN ANAK MILIK ORGANISASI MASYARAKAT ISLAM DI PROVINSI DAERAH KHUSUS IBUKOTA (DKI) JAKARTA - Budiharjo Budiharjo (State Institute of Islamic Studies (IAIN) Palu, 2015)
This article attempts to elaborate and to explore the educational background of caregivers in the Social Orphanage Children (PSAA) which belongs to the social Islamic organizations (CSOs) in the Province of Jakarta. The study which was conducted in Jakarta applied a survey method. There are 35 (thirty five) respondents from nine (9) PSAA who participated in this research. The study found that caregivers do not fully follow the principle of professionalism in the work. It can be identified by the education of the caregiver that the majority of caregivers only graduated from senior high school which is amounted to 71.43% and 28.57% of caregivers had received training related to child care and only 2.86% of caregivers who have an educational background in social work or social welfare. These will potentially cause the child to be in one cycle of misguided, thus inhibiting the development of the child.